THE IMPACT OF LIABILITY CLASSIFICATION ON THE ACCOUNTING PROCESS AND THE FORMATION OF ENTERPRISE REPORTING - VALKOVA, Nataliia; OVOD, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the modern context, managing a company's economic activities requires an accurate and comprehensive approach to liability accounting, as liabilities are a critical component of the sources of asset formation and directly influence the company’s financial stability and liquidity. Liabilities are an integral element of the enterprise's financial relationships with other economic entities, government authorities, employees, and others, necessitating precise accounting and timely settlement.The article analyzes contemporary approaches to the classification of liabilities, identifies problematic aspects of accounting for specific types of liabilities, systematizes existing classification methods, and examines the appropriateness of applying particular classification criteria. The impact of liability classification on the accounting process, the preparation of financial statements, the adoption of operational and strategic management decisions, and the analysis of the enterprise’s financial condition is also explored. It is proposed to distinguish between debts owed to foreign suppliers based on their attribution to operating or non-operating activities to simplify the accounting process for income and expenses arising from the revaluation of foreign currency debts at the balance sheet date. The necessity of classifying liabilities by their maturity dates is substantiated to facilitate the planning of cash flow formation and usage during the enterprise’s operations.The classification of liabilities is a vital component of the accounting process that significantly affects the quality of accounting information and management decision-making. Proper classification helps avoid errors in liquidity calculations, simplifies the accounting process, enhances internal control, and ensures the reliability of financial reporting. Future research should focus on developing methods for detailed accounting of specific types of liabilities, which would improve the transparency and relevance of financial information for various user categories.
Keywords: liabilities; collateral; liability classification; liability accounting